Low cost CE-NMR with microcoils for chemical detection - Adams, Kristl L.; Klunder, Greg; Demas, Vasiliki; Malba, Vince; Bernhardt, Anthony; Evan, Lee; Harvey, Chris; Maxwell, Robert; Herberg, Julie L. (Diffusion Fundamentals, 2009)
Understanding speciation in solids and solutions is important for environmental and toxicological purposes. Capillary electrophoresis (CE) is a simple rapid separation technique that can be used to identify species in solution. CE is particularly is well suited for rapid separations of metal containing samples. Direct on-capillary measurement of metal compound speciation can be obtained with nuclear magnetic resonance (NMR). The development of a low-cost microcoil CE-NMR system for in situ characterization of samples of interest is discussed. High precision laser lithography is used to produce copper sputtered microcoils that have comparable resistivity and quality factors to that of hand wound microcoils. A portable NMR system coupled with a CE system has the potential to identify chemical species in aqueous solutions. In addition, transient isotachophoresis can separate and pre-concentrate samples of interest to obtain separate chemical peaks for speciation by online NMR analysis. We are developing separation assays to determine the speciation of chemical complexes in solutions with minimal perturbation to the original sample equilibrium. On-line NMR measurements will be made downstream of the UV detector.